Room guest satisfaction towards guestroom physical environment quality in the theme hotel - Atikah Shahira Mohd Ali; Shahirah Shah Nurin; Zurinawati Mohi (School of Tourism, Universitas Ciputra Surabaya, 2023)
Guestroom design is essential in any hotel industry that can attract potential new guests. One of the advantages of a unique and memorable pleasant guestroom design is increasing revenue and profit for hotel operations. Today, many guestroom designs can merge with room guest satisfaction. Many themes and colors can enhance guest preferences to stay in the hotel. This study investigates the relationship between guestrooms' physical environment quality dimensions (i.e., guestroom ambiance, guestroom layout, guestroom cleanliness, guestroom furnishing, and guestroom lighting) towards room guest satisfaction. One hundred forty-five questionnaires were collected from the guest who stayed at a theme hotel; however, only 136 met the preliminary screening and were acceptable to test hypothesized relationships among the physical environment quality dimensions towards room guest satisfaction. The data were analyzed using multiple regression analysis. The study's result indicated significant relationships between guestroom ambiance, guestroom layout, guestroom cleanliness, guestroom furnishing, guestroom lighting, and room guests’ satisfaction. The outcome of this paper suggests that the hotel industry improve their design in hotel guestrooms and the hotel designers for upcoming build new hotels.